2014
DOI: 10.2147/opth.s67894
|View full text |Cite
|
Sign up to set email alerts
|

Acute-onset postoperative endophthalmitis caused by multidrug-resistant Klebsiella pneumoniae

Abstract: The purpose of this paper is to report outcomes of intravitreal imipenem in the treatment of multidrug-resistant Klebsiella-related postoperative endophthalmitis. This observational case series consists of three eyes from three patients seen between 2013 and 2014. Multidrug-resistant Klebsiella pneumoniae is characterized by a rapid, fulminant course and severe intraocular inflammation. Intravitreal imipenem may be used to treat such infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although percutaneous drainage was not performed and the blood culture was negative, it is still reasonable to believe that the patient in this case suffered from disseminated HVKP infections secondary to liver abscesses. Although previous cases have reported a poor visual outcome [25], appropriate empirical therapy with intravenous and intravitreal imipenem was utilized immediately and the visual outcome of the patient was improved in the current case. Therefore, carbapenem should be the first choice in the treatment of endophthalmitis caused by ESBL-producing HVKP strains.…”
Section: Discussionmentioning
confidence: 84%
“…Although percutaneous drainage was not performed and the blood culture was negative, it is still reasonable to believe that the patient in this case suffered from disseminated HVKP infections secondary to liver abscesses. Although previous cases have reported a poor visual outcome [25], appropriate empirical therapy with intravenous and intravitreal imipenem was utilized immediately and the visual outcome of the patient was improved in the current case. Therefore, carbapenem should be the first choice in the treatment of endophthalmitis caused by ESBL-producing HVKP strains.…”
Section: Discussionmentioning
confidence: 84%
“…In a case series of endophthalmitis caused by multi-drug resistant gram-negative organism in 3 patients, isolates were found to be susceptible only to imipenem. 55 The visual outcomes were generally poor (phthisis bulbi in 2 patients and optic atrophy in one patient). Dave et al 11 recently reported 11 cases of endophthalmitis with ceftazidime resistant gram-negative organisms which were managed by intravitreal imipenem.…”
Section: Alternative Intravitreal Antimicrobialsmentioning
confidence: 94%
“…Bacteria were selected based on a review of the current literature on MDR endophthalmitis. [4][5][6][8][9][10][11][12] These included MRSA, MRSE, Pseudomonas aeruginosa, carbapenem-resistant (CRE) and extendedspectrum b-lactamase (ESBL) Klebsiella pneumoniae, and vancomycin-resistant Enterococcus faecalis. Streptococcus pneumoniae acted as a nonresistant control.…”
Section: Methodsmentioning
confidence: 99%
“…9 Klebsiella, Enterococcus, and Pseudomonas species have increasing levels of antibiotic resistance globally and, although rare, are associated with poor outcomes in endophthalmitis. [10][11][12] Numerous strategies have been adopted to reduce the incidence of postoperative endophthalmitis. These include strategies to eliminate bacteria from the ocular surface, elimination of entry of organisms into the eye, and postoperative antibiotics and careful surgical planning and patient selection.…”
mentioning
confidence: 99%
See 1 more Smart Citation